Age Determination of Scardinius Erythrophthalmus (Cyprinidae) Inhabiting Bafra Fish Lakes (Samsun, Turkey) Based on Otolith Readings and Marginal Increment Analysis - Gümüş, A.; Bostanci, D.; Yilmaz, S.; Polat, N. (Soc Francaise d Ichtyologie, 2007)
Age and growth of Scardinius erythrophthalmus (Linnaeus, 1758) collected from Bafra Fish Lakes between January 2000 and December 2000 were determined by examination of five hard structures. Scales, vertebrae, opercular bones, lagenar and utricular otoliths were aged by three readers independently. The precision in age estimations, which is derived by percent reader agreement and coefficient of variation indicated that otoliths were the most reliable structures for age determination. The estimated ages ranged from two to five years. The radius length of each annulus was measured in lagenar and utricular otoliths and the mean values per age were calculated. Otolith dimensions were found to be highly correlative with the fork length. The weight-length relationship of S. erythrophthalmus was described as W = 0.0105FL 3.23 (r = 0.98) for combined sexes. Monthly changes in the frequency of appearance of an opaque margin on the outer edge of the otolith and the annual variation of marginal increment length indicated that only one growth zone formed from March to October per year.
Keywords: Age; Bafra Lake; Cyprinidae; Marginal Increment; Otolith; Scardinius Erythrophthalmus; Turkey